Microleakage of conventional, resin-modified, and nano-ionomer glass ionomer cement as primary teeth filling material - Dita Madyarani; Prawati Nuraini; Irmawati Irmawati (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: Glass ionomer cements are one of many dental materials that widely used in pediatric dentistry due to their advantage of fluoride release and chemical bond to tooth structure. Adherence of the filling material to the cavity walls is one of the most important characteristic that need to be examined its effect on microleakage. Purpose: This study was conducted to examine the microleakage of nano-ionomer glass ionomer cement compared with the conventional and resin-modified glass ionomer cements. Methods: Standard class V cavities sized 3 mm x 2 mm x 2 mm were made on a total of 21 extracted maxillary primary canine teeth and restored with the conventional, resin-modified, dan nano-ionomer glass ionomer cements. All the teeth were immersed in a 2% methylene blue dye for 4 hours. The depth of dye penetration was assessed using digital microscope after sectioning the teeth labio-palatally. The results were statistically analyzed using Kruskal-Wallis test. Results: All type of glass ionomer material showed microleakage. Conventional glass ionomer cement demonstrated the least microleakage with mean score 1.29. the resin-modified glass ionomer cements (mean score 1.57) and nano-ionomer glass ionomer cement (mean score 2.57). Conclusion: The conventional glassionomer, resin modified glassionomer, and nano-ionomer glassionomer showed micro leakage as filling material in primary teeth cavity. The micro leakage among three types was not significant difference. All three material were comparable in performance and can be used for filling material but still needs a coating material to fill the microleakage.Latar belakang: Semen ionomer kaca adalah salah satu dari banyak bahan gigi yang banyak digunakan dalam praktek kedokteran gigi anak karena bahan tersebut merilis fluoride dan berikatan kimia dengan struktur gigi. Perlekatan bahan tumpatan pada dinding kavitas adalah salah satu karakteristik paling penting yang perlu diteliti efeknya terhadap kebocoran mikro. Tujuan: Penelitian ini dilakukan untuk meneliti kebocoran mikro nano-ionomer glass ionomer dibandingkan dengan glass ionomer konvensional dan resin-modified. Metode: Standard kelas V kavitas berukuran 3 mm x 2 mm x 2 mm dibuat pada total 21 gigi kaninus sulung rahang atas hasil pencabutan dan ditumpat dengan glass ionomer tipe konvensional, resin-modified, dan nano-ionomer. Kemudian semua gigi direndam dalam 2% metilen biru selama 4 jam. Setelah gigi dibelah labio-palatal kedalaman penetrasi pewarna dinilai menggunakan mikroskop digital. Hasil dianalisis secara statistik menggunakan uji Kruskal-Wallis. Hasil: Semua jenis bahan glass ionomer menunjukkan kebocoran mikro. Glass ionomer tipe konvensional menunjukkan kebocoran mikro terendah dengan rata-rata skor 1,29; glass ionomer tipe resin-modified (rata-rata 1,57) dan glass ionomer tipe nano-ionomer (rata-rata skor 2.57). Hasil uji statistik menunjukkan kebocoran pada tepi ketiga bahan tersebut tidak berbeda secara signifikan. Simpulan: Bahan tumpatan glass ionomer tipe konvensional, resin-modified, dan nano-ionomer, ketiganya menunjukkan kebocoran tepi tumpatan yang tidak berbeda signifikan. Ketiga bahan yang sebanding dalam performance dan dapat digunakan untuk bahan tumpatan tapi masih membutuhkan bahan pelapis untuk mengisi kebocoran mikro yang terjadi.